E-portfolios supporting primary students' writing performance and peer feedback - Iolie Nicolaidou (My University, 2013)
E-portfolios show great promise for supporting students' writing performance and facilitating peer feedback, but empirical research of their use in primary education is limited. To address this gap, a yearlong study was conducted in a 4th grade primary class in Cyprus implementing e-portfolios (n = 20) to help students document their progress and send feedback to peers. A generic, open source weblog tool localized into Greek was used as an e-portfolio tool. Data sources included 176 student-essays, 1306 instances of peer feedback, students pre- and post-tests on writing performance, nine videotaped student interviews and one teacher interview. A paired samples t-test analysis showed that there was a statistically significant difference between students' pre-test (M = 62.6, SD = 9.82, n = 20) and post-test (M = 76.5, SD = 12.6, n = 20) on writing performance (t (19) = −8.03, p < .01). A repeated measures analysis of variance on e-portfolio artifacts showed that there were learning gains with respect to students' writing performance over time [F(4.01, 76.25) = 31.59, p < .01, η2 = 0.89]. A qualitative analysis of students' comments showed that students provided more thorough peer feedback over time and became gradually more capable of providing corrective feedback. The qualitative analysis of student interviews provided evidence that students valued peer feedback in their portfolios. The analysis of the teacher interview showed that average and high-ability students benefited the most from peer feedback. This study provided evidence that e-portfolios can support the development of students' writing performance and peer feedback skills in the context of primary school essay writing. Instructional implications for portfolio implementation are offered.
Keywords: E-portfolios; Writing performance; Peer feedback; Elementary education; Pedagogical issues